혁신클러스터 활성화 요인에 대한 정책공급자와 수요자의 인식차이 분석: 대덕연구개발특구 사례에 대한 AHP 조사를 중심으로 - 박후근(Park, Hwogeun); 배관표(Bae, Kwanpyo) (벤처창업연구, 2021)
The innovation cluster is formed by cooperation and networking among a number of actors, including companies, universities, research institutes, government and other supporting organizations, but the main subject of innovation in the venture ecosystem, which can be said to be the core of the innovation cluster, is the enterprise. Therefore, enterprises in innovation cluster can be seen as a major user of the innovation cluster policy. In order for the policy to be executed smoothly, policy acceptance is important. However, existing research on policy prioritization tends to be centered on policy providers, so it is necessary to check them from the perspective of policy users. Accordingly, this study conducted discussions from a two-way perspective to establish the correct policy direction through a balanced perspective between a policy provider-centered top-down perspective and a policy user's bottom-up perspective. First, the factors for activating the innovation cluster (three factors in the first level and 14 factors in the second level) were derived through prior research and expert interviews. After that, the importance of the factors for activating the innovation cluster was analyzed using AHP (Analytic Hierarchy Process) for the policy provider group and the user group in the Daedeok Innopolis, a representative case of innovation cluster policy. As a result of analyzing the importance of the innovation cluster activation factors from the perspectives of policy providers and users, some similarities were also seen, but overall differences in mutual perception were found. It was found that the policy provider group focused on innovation creation factors, while the policy user group viewed innovation creation, clusters, and industrial location factors from a more balanced perspective. This study is meaningful in that it deals with both perspectives in a balanced way by expanding the targets from the existing policy provider-centered research to policy users. In addition, practical contributions exist in the aspect of providing basic data so that policies can be carried out based on corporate needs in fostering innovation clusters. 혁신클러스터는 기업, 대학, 연구기관, 정부 및 기타 지원기관 등 다수의 주체들 간 협력과 네트워킹에 의해 구성되지만, 혁신클러스터의 핵심이라고 할 수 있는 벤처생태계에 있어 혁신의 주요 주체는 바로 기업이다. 그렇기 때문에, 혁신클러스터에 입주한 기업은 혁신클러스터 정책의 주요한 수요자로 볼 수 있다. 정책이 원활히 수행되기 위해서는 정책수요자의 정책 수용(acceptance)이 중요하다. 그러나 정책 우선순위 결정에 관한 기존의 연구는 정책공급자 중심으로 이루어지는 경향이 있어, 정책수요자 관점에서의 점검이 필요하다. 이에 따라, 본 연구는 정책공급자 중심의 하향식 관점(top down)과 정책수요자의 상향식 관점(bottom up) 간 균형적 시각을 통해 올바른 정책방향을 수립하기 위해 양방향의 관점에서 논의를 진행하였다. 먼저, 선행연구와 전문가 면담 등을 통해 혁신클러스터 활성화 요인(1계층 3개 요인, 2계층 14개 요인)을 도출했다. 이후, 혁신클러스터 정책의 대표 사례인 대덕연구개발특구의 정책공급자 그룹과 수요자 그룹을 대상으로 혁신클러스터 활성화 요인의 중요도를 AHP(Analytic Hierarchy Process)를 이용하여 분석했다. 혁신클러스터 활성화 요인에 대해 정책공급자와 수요자 관점에서 중요도를 분석한 결과 일부 유사점도 보이나, 전반적으로는 상호 인식의 차이가 존재하는 것을 확인할 수 있었다. 정책공급자 그룹은 혁신창출 요인에 집중하는 반면, 정책수요자 그룹은 보다 균형적인 시각에서 혁신창출, 클러스터, 산업입지 요인을 바라보고 있는 것으로 조사되었다. 본 연구는 기존의 정책공급자 중심의 연구에서 정책수요자까지 대상을 확대하여 양 관점을 균형있게 다루었다는 점에서 의의가 있다. 또한 혁신클러스터 육성에 있어 기업 니즈 중심으로 정책이 수행될 수 있도록 기초자료를 제공한다는 측면에서 실무적인 기여도 존재한다.